Implementasi Program Employee Relations untuk Meningkatkan Motivasi Kerja Karyawan di Bank Perkreditan Rakyat (BPR) Nusumma Yogyakarta - Al Musa Karim; Revian Afrilia (Universitas Muhammadiyah Klaten, 2024)
This research aims to analyze employee relations activities to increase employee motivation at Bank Perkreditan Rakyat (BPR) Nusumma Yogyakarta. One form of relationship in public relations is employee relations or employee relations, employee relations aims to manage harmonious relationships and communication that occurs within a company to be able to achieve the company's vision and mission. The method in this research is descriptive qualitative with the data analyzed are the results of documentation, literature study and the results of interviews with the operational manager of BPR Nusumma Yogyakarta and Human Resource (HR) BPR Nusumma Yogyakarta. The results of the study show that BPR Nusumma Yogyakarta has implemented various employee relations programs, both formal and informal programs. The employee relations program implemented at BPR Nusumma Yogyakarta targets to increase the intrinsic and extrinsic motivation of employees, one of which is through an award program in the form of providing intensive for employees who successfully achieve the targets given by the company.